The Effectiveness of China - Russia Energy Cooperation Through the Development of Nuclear Power Plants (NPP) In Addressing Global Warming Issues In China - Thariq Al Fadhil (Mediasi: Journal of International Relations, 2022)
China is the largest country in carbon gas emissions in the world, which is because China isthe country that consumes the largest coal in the world as an energy source for power plants.Too large carbon gas emissions will have an impact on global warming and will result inenvironmental damage. China is cooperating with Russia in the construction of a NuclearPower Plant (PLTN) which aims to overcome the problem of global warming in China. Theauthor's aim in the research is to analyze the effectiveness of China's cooperation with Russiathrough the construction of NPP as alternative energy and solutions in overcoming the globalwarming problem that occurs in China. This research uses a qualitative research method thatwill explain the problem and analyze it by looking at scientific studies related to the research.The result of this research is that nuclear power plants are able to effectively overcomeenvironmental problems or global warming that occurs in China. This can be seen from Chinawhich began to experience a slowdown in the amount of carbon gas emissions from 2011 to2021 and China has also experienced a decrease in air pollution since 2013, which originallyPM2.5 in China was 85 micrograms per metercubic and continued to decline until in 2022PM2.5 in China was 30 micrograms per metercubic. This is because China is reducing coalenergy consumption and increasing nuclear energy in power plants.